Enhancing and stabilizing monoclonal antibody production by Chinese hamster ovary (CHO) cells with optimized perfusion culture strategies - Liang, Kexue; Luo, Hongzhen; Li, Qi (Frontiers in Bioengineering and Biotechnology, 2023)
The perfusion medium is critical in maintaining high cell concentration in cultures for the production of monoclonal antibody by Chinese hamster ovary (CHO) cells. In this study, the effects of perfusion culture strategies when using different media on the process stability, product titer, and product quality were investigated in 3-L bioreactor. The results indicated that continuous perfusion could maintain higher levels of cell density, product titer, and quality in comparison with those of the intermittent perfusion culture. Next, the perfusion culture conditions with different perfusion rates and temperature reduction methods were further optimized. When combining the high perfusion rates and delayed reduction of culture temperature at day 6, the product titer reached a higher level of 16.19 g/L with the monomer relative abundant of 97.6%. In this case, the main peak of the product reached 56.3% and the total N-glycans ratio was 95.2%. To verify the effectiveness of the optimized perfusion culture in a larger scale, a 200-L bioreactor was used to perform and the final product titer reached the highest level of 16.79 g/L at day 16. Meanwhile, the product quality (monomer abundant of 97.6%, main peak of 56.3%, and N-glycans ratio of 96.5%) could also be well maintained. This study provided some guidance for the high-efficient production of monoclonal antibody by CHO cells via optimized perfusion culture strategy.